2019
DOI: 10.3390/nu11030664
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidin—Cell Wall Interactions within Apple Matrices Decrease the Metabolization of Procyanidins by the Human Gut Microbiota and the Anti-Inflammatory Effect of the Resulting Microbial Metabolome In Vitro

Abstract: B-type oligomeric procyanidins in apples constitute an important source of polyphenols in the human diet. Their role in health is not known, although it is suggested that they generate beneficial bioactive compounds upon metabolization by the gut microbiota. During apple processing, procyanidins interact with cell-wall polysaccharides and form stable complexes. These interactions need to be taken into consideration in order to better assess the biological effects of fruit constituents. Our objectives were to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 64 publications
(90 reference statements)
0
33
0
Order By: Relevance
“…One of their beneficial health effects is the prevention of oxidation of lipids and proteins in the stomach (Boléa, Ginies, Vallier, & Dufour, 2019; Gobert et al., 2014; Lee et al., 2020). Furthermore, many recent studies have shown that CPS–polyphenol complexes have a positive effect in the colon (Grant et al., 2020; Kardum & Glibetic, 2018; Le Bourvellec et al., 2019; Monfoulet et al., 2020; Phan et al., 2020; Tarko & Duda‐Chodak, 2020). Polyphenols can be released from their complexes through the action of enzymes or microorganisms in the intestinal tract and biotransformed by the colonic microbial metabolism (i.e., from the nonabsorbable to the absorbed form).…”
Section: The Participants In the Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of their beneficial health effects is the prevention of oxidation of lipids and proteins in the stomach (Boléa, Ginies, Vallier, & Dufour, 2019; Gobert et al., 2014; Lee et al., 2020). Furthermore, many recent studies have shown that CPS–polyphenol complexes have a positive effect in the colon (Grant et al., 2020; Kardum & Glibetic, 2018; Le Bourvellec et al., 2019; Monfoulet et al., 2020; Phan et al., 2020; Tarko & Duda‐Chodak, 2020). Polyphenols can be released from their complexes through the action of enzymes or microorganisms in the intestinal tract and biotransformed by the colonic microbial metabolism (i.e., from the nonabsorbable to the absorbed form).…”
Section: The Participants In the Interactionsmentioning
confidence: 99%
“…Although many NEPPs and complex polyphenols, for example, proanthocyanidins, have very low bioavailability in the upper gut, their resulting metabolites (mostly phenolic acids), produced by the colonic microbiota, are highly available (Aura et al., 2013; Palafox‐Carlos, Ayala‐Zavala, & González‐Aguilar, 2011; Saura‐Calixto et al., 2010). This process can also be modulated by interactions with CPSs, both noncovalent and covalent (Le Bourvellec et al., 2019; Saura‐Calixto, 2011). Compared to unbound polyphenols, interactions with CPSs reduce the degradation of procyanidins during digestion and the production of anti‐inflammatory bioactive metabolites, but favor butyrate production, which is known for its beneficial effects on health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Covalent or noncovalent binding of proanthocyanidins with cell wall polysaccharides significantly reduced the degradation effect of human intestinal flora on proanthocyanidins. However, when there was no binding between proanthocyanidins and cell wall polysaccharides, the best anti‐inflammatory effect was achieved (Le Bourvellec et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Three OTUs (146, 393 and 1761) derived from the 16S rDNA V3-V5 region were identified in a previous in vitro study [23] involving four microbial faecal communities that were incubated with a mixture of purified apple polyphenols and polysaccharides (Data S1, available in the online version of this Fig. 1.…”
Section: Full-length 16s Rrna Gene Recovery From Short Metabarcoding Sequencesmentioning
confidence: 99%